Juxtaposing the influence of nuclear energy, human development index and research & development on economic performance of the European Union countries - Deka, Abraham; Kipulu, Joshua Kisungu; Dube, Sindiso (Environmental progress & sustainable energy, 2025)
Nuclear energy has emerged as one of the essential sources of energy in the European Union (EU) region. It does not cause pollution to the environment, just like renewable energy (RE), though it is subject to depletion. Therefore, nuclear energy – a low‐carbon energy source – is fundamental in maintaining sustainable development through raising national income with less ecological harm. However, there are studies that have investigated the influence of nuclear energy on the economic performance and on environmental sustainability. Thus, to cover the existing gap and inform policy making this study investigates the influence of nuclear energy and research & development (necessary for technological innovations) on the economic performance of the EU countries. The data of fourteen EU nuclear energy consuming countries is used in this analysis for the period 1990 to 2015. Important determinants of economic growth – capital, RE, human capital and financial development – are specified in the model for model controlling purposes. To achieve the research aim, the Generalized Least Squares and the Panels Correlated Standard Errors that caters for the within‐panel correlations are used. The findings depict that nuclear energy, research & development, human development index and financial development are fundamental in raising the economic growth of the EU countries. However, capital growth rate and renewable energy are counterproductive. This research informs policy implication in nuclear energy use along with technological innovations and human development in order to advance sustainable economic growth.